Ovarian cancer arising from the proximal fallopian tube in a patient with a BRCA2 mutation - Badiner, Nora; Nchako, Corbyn M.; Ma, Lucy; Frey, Melissa K. (Gynecologic oncology reports, 2021)
•BRCA1/2 carriers are at high risk for fallopian tube carcinoma, which can arise in the proximal fallopian tube.•Pathologic analysis of RRBSO specimens should include serial sectioning of the entire tube, not just the fimbriated end.•Concurrent hysterectomy at time of RRBSO may be considered to ensure all tubal epithelium is resected. Patients with BRCA mutations are at high risk of high grade serous ovarian cancer. A paradigm shift has resulted in the current understanding that many cases of ovarian cancer actually arise from the fimbriated fallopian tube. The case presented here involves fallopian tube carcinoma arising from the cornua of the uterus in a BRCA2 carrier. This case suggests that pathologic analysis of risk-reducing bilateral salpingo-oophorectomy (RRBSO) specimens via serial sectioning and extensively examining the fimbriated end (SEE-FIM) may be insufficient to diagnose all occult lesions of interest. This case also provides a new consideration in the ongoing debate over the role of concurrent hysterectomy at time of RRBSO in BRCA carriers.